Polar lipid profile of Saccharina latissima, a functional food from the sea - Rey, Felisa (2019)
Increasing global demand for food has generated a need for new strategies to feed a fast-growing population. Oceans appear as a sustainable solution, providing alternative sources of food such as macroalgae. These sea vegetables have high nutritional value and provide functional and health benefits. The sugar kelp Saccharina latissima is an emerging edible seaweed used mainly for human consumption. Although much is known about its biochemical compositions its lipidome remains unexplored. The aim of the present study was to characterize the polar lipid profile of S. latissima using a lipidomic-mass spectrometry HILIC-LC-MS based analysis. This approach allowed the identification of 197 molecular species of polar lipids, including glycolipids, phospholipids and betaine lipids. Several molecular species identified are carriers of polyunsaturated fatty acids with nutritional value and have been reported with anti-inflammatory, anti-microbial and anti-proliferative activity. Saccharina latissima is an emerging candidate to promote blue biotechnology inspired by the ocean.